Analisis Efektivitas Elektronifikasi Pembayaran Tol untuk Mengurangi Kemacetan pada Gerbang Tol di Indonesia - Rafiq Hakim; Achmad Rozan; Rimi Gusliana Mais; Uun Sunarsih (Universitas Galuh, 2026)
One of the Indonesian government's initiatives in the digitalization of public services is the implementation of electronic toll payment (electronic toll collection). This innovation is intended to make toll road transactions more convenient for users while reducing traffic congestion at toll gates. The objective of this study is to analyze the effectiveness of electronic toll payment implementation and identify the challenges encountered in its application. This study employs a Literature Review method. The findings indicate that electronic toll payment provides numerous benefits to toll road users, including eliminating the need to carry cash and reducing waiting times at toll gates. However, several challenges remain, such as limited public familiarity with Electronic Toll (e-Toll) cards and similar payment systems. Another issue is the frequent occurrence of malfunctioning (error) electronic toll card readers at some toll gates. To address these challenges, the government should conduct public awareness and education campaigns regarding electronic toll payment systems and provide competent technical personnel to handle operational issues related to electronic toll card readers. In conclusion, the implementation of electronic toll payment has significantly improved convenience for the public. Nevertheless, the government must continue addressing the remaining obstacles by enhancing public education and ensuring the availability of adequate human resources to support the optimal operation of the system.